Pengaruh Gaya Kepemimpinan Otoriter dan Lingkungan Kerja Non Fisik terhadap Kepuasan Kerja Karyawan PT. Nikomas Gemilang Divisi Nike Bagian Cutting - Calvin Mahesa Galih; Riki Gana Suyatna; Rosnia Rosliana; Anggi Prayoga (Universitas 45 Surabaya, 2024)
This study aims to determine and analyze whether there is an effect of authoritarian leadership style and non-physical work environment partially and simultaneously on employee job satisfaction at PT. Nikomas Gemilang Nike Division Cutting Section. This research method uses correlational quantitative methods and the sampling technique uses a saturated sample technique. Based on the results of calculations with the t test, the value of tcount>ttable (2,611 > 2,026), it was obtained that the Authoritarian Leadership Style had a significant effect on Job Satisfaction, based on the results of calculations with the t test, the value of tcount>ttable (3.783 > 2,026), it was obtained that the Environment Non-Physical Work has a significant effect on Job Satisfaction. Based on the f test, the value of Fcount>Ftable or (56.094 > 3.251), it can be concluded that simultaneously Authoritarian Leadership Style and Non-Physical Work Environment have a significant effect on Job Satisfaction.